PENGARUH MODEL PROBLEM-BASED LEARNING BERBANTUKAN DIGITAL QUIZIZZ TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN SELF-EFFICACY SISWA - Manalu, Meyanti; Hasratuddin, Hasratuddin; Ramdhani, Sendi; Syahril, Syahril (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This research aims to analyze the impact of the Problem-Based Learning (PBL) model assisted by digital Quizizz on the mathematical critical thinking ability and Self-efficacy of fifth-grade elementary school students in Percut Sei Tuan District. The study employed an experimental design using a Non-equivalent Control Group Design. The sample consisted of students from SDN 105293 and SDN 101778 Medan Estate. Data collection included pretests and posttests on critical thinking skills, as well as pre- and post-tests on self-efficacy. Data analysis was conducted using Hotelling’s T2 test and two-way ANOVA. The results revealed that the PBL model assisted by Quizizz significantly enhanced students' mathematical critical thinking abilities and self-efficacy. However, no interaction was found between the learning model and students' initial abilities in both variables. These findings suggest that technology integration in education can effectively improve students’ learning outcomes, particularly in fostering critical thinking and students’ academic confidence.